Modeli diskretne izbire - Kerbler, Boštjan Kefo (Urbani izziv, 2006)
The paper systematically describes special regression methods - discrete choice models - known as probability models. The meaning of models and their methodological characteristics are described, as well as different types of models, especially binary-choice models and censored regression models. We considered three most commonly used approaches to estimating such models - logit, probit and tobit model.
Keywords: logistični modeli; regresijska analiza; statistične metode